The Role of Micronutrients in Human Immunodeficiency Virus Infection: A Narrative Review - Putu Evindya Vipascitadewi Nandanaya Bharata; I. G. A. A. Elis Indira; Ni Made Dwi Puspawati; Anak Agung Gede Kresna Naria Putra (Warmadewa University, 2026)
Human Immunodeficiency Virus (HIV) remains a major global health burden, with micronutrient deficiency being a frequent complication that worsens disease progression. Deficiencies in vitamins A, D, E, and zinc have been linked to impaired immune responses, increased susceptibility to opportunistic infections, and poor treatment outcomes. This narrative review aims to explore the role of micronutrients, particularly vitamins A, D, E, and zinc, in the clinical course and management of HIV infection. A literature-based narrative review was conducted using PubMed, Scopus, and Google Scholar. Articles discussing the association between micronutrients and HIV progression, immune response, and treatment outcomes were synthesized. A total of 847 articles were initially identified; after screening and applying inclusion criteria, 42 articles were included in this review. Evidence shows that vitamin A influences mucosal immunity and reduces mother-to-child transmission; vitamin D modulates immune cell proliferation and autophagy; vitamin E acts as an antioxidant reducing oxidative stress; and zinc supports T-cell function and reduces opportunistic infections. Vitamin D supplementation significantly increased serum 25(OH)D levels (p<0.0001) but did not significantly alter CD4 counts or viral load in clinical trials. Overall, supplementation outcomes remain inconsistent. While multiple micronutrient supplementation may improve immune markers, its impact on mortality and viral load reduction is still inconclusive. Micronutrient deficiency is common among HIV patients and negatively affects disease progression. Although supplementation may improve nutritional and immunological status, robust evidence regarding long-term survival and virological outcomes is lacking. Further high-quality studies are required to establish clear recommendations.